Aktivitas Antibakteri Ekstrak Akar Mengkudu (Morinda citrifolia L.) terhadap Pertumbuhan Vibrio cholerae - Yohana Makaborang (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
One of the infectious and deadly human diseases caused by bacteria is cholera or acute diarrhea, caused by Vibrio cholerae. This disease is very dangerous and needs to be treated properly and quickly. This study aims to determine the anti-bacterial activity of noni root extract (Morinda citrifolia L.) on the growth of Vibrio cholerae. This type of experimental research uses a completely randomized design (CRD). The data collected in this study was the diameter of the inhibition zone measured from each treatment. The results of the ANOVA test showed that the noni root extract tested on Vibrio cholerae after being analyzed, obtained Fcount > Ftable, namely 53.929 > 3.48. Noni root extract has inhibitory power against the growth of Vibrio cholerae. The results of this study proved that the diffusion method used showed good results, which was indicated by the presence of inhibition zones in all five treatments (5%, 15%, 20%, 25%, and 50%). The best treatment was at a concentration of 50% with an inhibition zone diameter of 28.66 mm.